Pharmacoeconomy of diabetes mellitus and its implications for organization and quality of the care in the Czech Republic - Horák, Pavel; Kvapil, Milan (European Journal for Biomedical Informatics, 2014)
Introduction: Organization of the care is important factor for success, cost effectiveness and quality of the care for large scale chronic diseases such as diabetes mellitus. Valid data are needed for decision support. Aim: To calculate real prevalence of diabetes in the population from incomplete data sources originally created for billing to the insurance company, to establish how these patients are treated and collect markers of quality of the care. Methods: In data sources diabetic patients were identified by combining diagnoses from coded procedures with data about medical prescription and procedures directly linked to diabetes. Results: 6% increase in real incidence rate of diabetes mellitus patients since 2002 was observed as well as 23% (2003-2009) decrease in mortality rate (50% decrease between 1980 to 2009).
Keywords: diabetes mellitus; Diabetes Mellitus; ekonomika a organizace zdravotní péče; disparity zdravotní péče; Diabetes Complications; Rural Population; Health Care Economics and Organizations; Česká republika; zdravotní pojištění; Health Care Surveys; Urban Population; sběr dat; náklady na zdravotní péči; venkovské obyvatelstvo; incidence; komplikace diabetu; Quality of Health Care; Healthcare Disparities; Czech Republic; Data Collection; Insurance, Health; lidé; Humans; průzkumy zdravotní péče; Health Care Costs; ekonomika farmaceutická; kvalita zdravotní péče; Incidence; městské obyvatelstvo; Economics, Pharmaceutical